Negative Affect and Impulsivity in Adolescents with Non-Suicidal Self-Injury: The Moderating and Mediating Roles of Perceived Social Support - Pan B; Gong Y; Guo M; Wang X; Lu H; Lin Z; Zhang B (Neuropsychiatric Disease and Treatment)
Bing Pan,1 Yun Gong,2 Meiyi Guo,3 Xiaohua Wang,1 Haitao Lu,1 Zheng Lin,1 Bingren Zhang3 1Department of Psychiatry, Second Affiliated Hospital, Zhejiang University School of Medicine, Zhejiang University, Hangzhou, 310009, People’s Republic of China; 2Department of Pediatrics, Hangzhou First People’s Hospital, Hangzhou, 310009, People’s Republic of China; 3Department of Medical Psychology, Affiliated Hospital (School of Clinical Medicine), Hangzhou Normal University, Hangzhou, 311121, People’s Republic of ChinaCorrespondence: Bingren Zhang, Department of Medical Psychology, Affiliated Hospital (School of Clinical Medicine), Hangzhou Normal University, Hangzhou, People’s Republic of China, Tel +13757148402, Email bingrenz@hznu.edu.cn Zheng Lin, Department of Psychiatry, Second Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, People’s Republic of China, Tel +13757118261, Email 2194026@zju.edu.cnBackground: Negative affective states and impulsivity have been found to be closely associated with non-suicidal self-injury (NSSI), but how negative affect contributes to impulsivity in NSSI adolescents and the role of perceived social support remain unclear.Methods: In Study 1, the Barratt Impulsiveness Scale (BIS-11) was administered on 225 NSSI adolescents and 225 healthy volunteers to determine the characteristics of impulsivity in the patients. In Study 2, 102 of the patients were randomly selected to further complete the Zung Self-rating Anxiety Scale (SAS), Zung Self-rating Depression Scale (SDS), and Multidimensional Scale of Perceived Social Support (MSPSS) to clarify the relationships between negative affect, perceived social support, and impulsivity in these patients.Results: In Study 1, NSSI adolescents scored higher than volunteers on almost all factors of BIS-11 except for Cognitive Instability. In Study 2, Support from significant others mediated the association between SAS and BIS-11 Self-control. Moreover, Support from significant others and family moderated the prediction of SAS score on their BIS-11 Cognitive Complexity.Conclusion: Compared to healthy adolescents, NSSI individuals were more impulsive, while perceived support from family and significant others prevented the anxious NSSI adolescents from lower cognitive complexity. Therefore, more social support should be available to NSSI adolescents with high anxiety to reduce their risk of self-harm due to high impulsivity.Keywords: adolescents, impulsivity, negative affect, non-suicidal self-injury, perceived social support